A Study on the application of Abraham Maslow's theory of motivation to first and second year nursing students in Davao City - Lopez, Ulyn G.
This research study which basically aims to apply Abraham Maslow's Theory of Motivation to the reasons of first and second year nursing students in Davao City in taking up BS Nursing. The course a student is taking up in college determines his/her future career or vocation. Nursing students will eventually become nurses by profession. For the past two years, there has been an increase in the demands for nurses abroad especially in the United States. The research determined the strongest reason theses nursing students have in choosing the course; then the reasons he associated then to the levels of Abraham Maslow's Hierarchy on Needs which determined the present needs theses nursing students have: psychological needs, safety and security needs, and needs of self actualization. Survey methods using purposive random sampling was employed gathering data such as socio-demographic background, reasons for taking up nursing, choice of school and questions regarding desire for overseas work, and migration, the target population were the first year and second year nursing students in the sis schools of Davao: Ateneo de Davao University, Brokenshire College, Davao Doctors College, Mindanao Medical Foundation College, San Pedro College, Tecarro College Foundation. The research also presents the implications of increase in nursing enrollment to overseas work, migration and nursing instruction.